Assessment of patients treated for head injury in the context of chronic disorders - Szewczak, Agnieszka (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Injured head injuries often leave long-term consequences in the form of permanent damage to the central nervous system and behavioral disorders. Aim The aim of this study is to present the assessment of patients treated for head injury in the context of chronic disorders. Material and method The study included 60 selectively selected patients of the hospital emergency department over 20 years after head injury. Results Among the respondents (60), 25 people, including 6 women and 19 men remained for further treatment in the hospital, 28 respondents, ie 8 women and 20 men applied for further treatment in a specialist clinic, and 7 respondents, including 1 woman and 6 men reported to see your GP for further treatment. Conclusions Patients after head injuries should be monitored for possible further post-traumatic complications by primary care physicians.